THE EFFECTIVENESS OF â€œNEURO-COGNITIVEâ€ LEARNING STRATEGY FOR INCREASING SPEAKING PERFORMANCE: STUDY ON NON-ENGLISH DEPARTMENT STUDENTS - Pratiwi, Widya Rizky; Suardi, Suardi; Acvfira, Lukytta Gusti (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2021)
English is the unifying international language of world communication. However, English-speaking countries face many problems in their position as a foreign language, so learning strategies and motivation must be emphasized in the learning process. On the other side, communication skills are the most needed skills to prepare for the world of work. Thus, this research with a qualitative method approach is focused on investigating the effectiveness of teaching and training on "Neurocognitive" based learning strategies, with continuous mentoring and injection of motivation. The instruments used are field note observations, questionnaires, interviews, and photo documentation. The subjects of this study were 14 students in the second semester of the 2020/2021 academic year of the Information Systems study program at STMIK Bina Adinata. The results showed that the students' cognitive and non-cognitive skills were improved, especially their speaking performance. However, even though the research team carried out the procedure for providing learning strategy training under the correct stages, the results obtained were less than optimal due to online learning conditions. So it is recommended for further researchers to continue this research by thinking about learning strategies that can be combined for offline and online needs.